Applying Digital Information Delivery to Convert Habits of Antibiotic Use in Primary Care in Germany: Mixed-Methods Study - Poss-Doering, Regina; Kuehn, Lukas; Kamradt, Martina; Glassen, Katharina; Wensing, Michel (JMIR Publications, 2020)
BackgroundAntimicrobial resistance is an important global health issue. In Germany, the national agenda supports various interventions to convert habits of antibiotic use. In the CHANGE-3 (Converting Habits of Antibiotic Use for Respiratory Tract Infections in German Primary Care) study, digital tools were applied for information delivery: tablet computers in primary care practices, e-learning platforms for medical professionals, and a public website to promote awareness and health literacy among primary care physicians, their teams, and their patients. ObjectiveThis study is embedded in the process evaluation of the CHANGE-3 study. The aim of this study was to evaluate the acceptance and uptake of digital devices for the delivery of health-related information to enhance awareness and change habits of antibiotic use in primary care in Germany. MethodsThis study used a convergent-parallel mixed-methods design. Audio-recorded semistructured telephone interviews were conducted with physicians, nonphysician health professionals, and patients in the CHANGE-3 program. Pseudonymized verbatim transcripts were coded using thematic analysis. In-depth analysis was performed based on the inductive category of information provision via digital information tools. Identified themes were related to the main postulates of Diffusion of Innovations theory (DIT) to provide an explanatory frame. In addition, data generated through a structured survey with physicians and nonphysician health professionals in the program were analyzed descriptively and integrated with the qualitative data to explore the complementarity of the findings. ResultsFindings regarding the acceptance and uptake of digital devices were related to three postulates of DIT: innovation characteristics, communication channels, and unanticipated consequences. Participants considered the provided digital educative solutions to be supportive for promoting health literacy regarding conversion of habits of antibiotic use. However, health care professionals found it challenging to integrate these solutions into existing routines in primary care and to align them with their professional values. Low technology affinity was a major barrier to the use of digital information in primary care. Patients welcomed the general idea of introducing health-related information in digital formats; however, they expressed concerns about device-related hygiene and the appropriateness of the digital tools for older patients. ConclusionsPatients and medical professionals in German primary care are reluctant to use digital devices for information and education. Using a Diffusion of Innovations approach can support assessment of existing barriers and provide information about setting-specific preconditions that are necessary for future tailoring of implementation strategies. Trial RegistrationInternational Standard Randomized Controlled Trial Number (ISRCTN) 15061174; http://www.isrctn.com/ISRCTN15061174.